Cartography in Modern Perspective (Discussion Note) - Thapa, Pawitra (Himalayan Review, 2009)
Cartography compasses a number of specialized phases: the scale of the mapping, the method of projection, the symbolization of the data being mapped, the map design, and the preparation of the map for duplication. Though the rate of change of technology in cartography is accelerating, nowadays it is seen as the medium of conveying of spatial information by means of maps. The main objective of this paper is to discuss the changing trend of cartography with some practical examples. Key words: visualization, cartography, spatial, GIS, changing technology. The Himalayan Review Vol. XXXVII, 2006 Page: 71-84